Sosialisasi dan Pendampingan Pemasaran Digital dalam Upaya Pemberdayaan Masyarakat, Pelaku UMKM Kripik Pisang di Kampung Kalicaah Desa Tanjung Jaya - Ulfi Jefri; Rismala Dewi; Selpi Anggreini Saputri; Seri Rahmawati; Alfiana Pratiwi; Shela Mitha Yani Putri (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2025)
Digital marketing outreach and mentoring in an effort to empower the community, particularly banana chip MSMEs, was carried out as a form of community service to create better economic turnover in Kalicaah Village. This activity began with the low capacity of MSMEs in utilizing digital technology as a medium for product promotion and distribution. Therefore, students were present as facilitators and mentors to improve digital literacy among the community, especially housewives and business owners in the area. The main focus of the activity was on digital-based marketing aspects, where the community was encouraged to rise up, create works that have sales value, and develop sustainable businesses based on local potential. The activity was carried out in two stages: the outreach stage and the mentoring stage. In the outreach stage, 20 participants attended a presentation on the importance of digital marketing for small business owners, including an introduction to online platforms such as marketplaces, social media, and Google Maps. This stage used a direct face-to-face method with a personal approach, so that participants could understand the concept more contextually. Next, in the mentoring stage, students conducted direct practice with snack food entrepreneurs. The assistance includes creating logo designs for packaging as a form of product branding, creating accounts on marketplaces (such as Tokopedia or Shopee), and registering business locations on Google Maps for wider consumer access. It is hoped that through this activity, MSMEs in Kalicaah Village will be able to increase their business competitiveness and expand their market through optimal use of digital technology. Furthermore, this activity also encourages the creation of sustainable, community-based economic independence through the use of digital technology.